Penerapan Manajemen Risiko dalam Aplikasi Maxim: Pendekatan ISO 31000 untuk Menjamin Keberlanjutan Layanan - Ardhani, Alvina Waihda (Universitas PGRI Semarang, 2025)
Risk management is a crucial aspect in the success of digital application management, including Maxim, which is an online transportation service. This study aims to analyze the implementation of risk management in the Maxim application with the ISO 31000 approach and qualitative methods. The steps in the study include risk identification, risk analysis, risk evaluation, and implementation of mitigation plans based on the ISO 31000 framework. Data were collected through interviews with related parties, document reviews, and operational observations of the application. The results of the analysis show that the main risks in the Maxim application include technical disruptions, user data leaks, and reputation risks due to inconsistent services. With the ISO 31000 systematic approach, this study offers strategic recommendations to mitigate these risks, ensure operational sustainability, and increase user trust in the Maxim application.